Endurance training changes the expression of miR-1 and miR-133 and predicted genes in slow and fast twitch muscles. (May 2023) - Bahrami, Farid; Fathi, Mohammad; Ahmadvand, Hassan; Pajohi, Naser
Highlights: Endurance training increased the expression of miR-133 in slow and fast twitch muscles. Endurance training decreased the expression of miR-1 in slow twitch, not in fast-twitch muscle. Besides decrease EDL muscle wet weight of the treated group due to endurance training, the rate of MEF2c and HDAC4 protein synthesis increased and decreased, respectively. The expression of hdac4 and mef2c genes in slow and fast twitch muscles to endurance training was different. Abstract: Purpose of the research: Endurance training can modify signaling and gene expression pathways that play a pivotal role in determining the phenotype of the fibers. The present study aimed to investigate the effects of endurance training on the expression of some myomiRs and related genes in slow and fast twitch muscles. Methods: Twenty healthy male adult Wistar rats (281 ± 14 g) were randomized to either control ( n = 10) or treated ( n = 10). The treated group performed an endurance program for eight weeks (running on a treadmill for eight weeks, 50 min, 23 m/min). After the end of the training protocol, the slow (soleus) and fast (EDL) twitch muscles were removed to assess the miR-1, miR-133 expression, and hdac4, mef2c genes, and protein by real-time PCR and western blot, respectively. Results: The soleus muscle miR-1 expression and mef2c gene in the treated group were significantly lower compared control ( p = 0.0001). In contrast, miR-133 and hdac4 gene expression of the soleus muscle of the treated group increased significantly ( p = 0001), and the EDL miR-133 and mef2c expression of the treated group increased in the compared control group ( p = 0.0001). The EDL MEF2c protein expression in the treated group significantly decreased compared to the control group, although the expression of EDL HDAC4 protein significantly increased ( p = 0.0001). Conclusions: Endurance training changes the expression of the miR-1, miR-133, and their predicted genes in slow and fast twitch muscles. Also, the rate of HDAC4 and MEF2c protein synthesis, which are upstream and downstream of these myomiRs, was affected by endurance training. Graphical abstract: Image, graphical abstract